Multi-gene phylogeny and taxonomy of the genus Bannoa with the addition of three new species from central China - Chun-Yue Chai; Chun-Yue Chai; Ting Lei; Xue-Ying Chu; Feng-Li Hui; Feng-Li Hui (Frontiers in Microbiology, 2023)
The genus Bannoa is a small group of ballistoconidium-forming yeasts in the family Erythrobasidiaceae (Cystobasidiomycetes). Prior to this study, seven species belonging to this genus have been described and published. In this study, phylogenetic analyzes of Bannoa based on the combined sequences of the small ribosomal subunit (SSU) rRNA gene, the internal transcribed spacer (ITS) regions, the D1/D2 domains of the large subunit rRNA gene (LSU) and the translation elongation factor 1-α gene (TEF1-α) were conducted. Three new species, namely B. ellipsoidea, B. foliicola, and B. pseudofoliicola, were delimited and proposed based on morphological and molecular evidence. B. ellipsoidea was found to be closely related to the type strains of B. guamensis, B. hahajimensis, and B. tropicalis, but with 0.7–0.9% divergence (4–5 substitutions) in the LSU D1/D2 domains and 3.7–4.1% divergence (19–23 substitutions and one−two gaps) in the ITS regions. B. foliicola was found to belong to the same clade as B. pseudofoliicola from which it differed by 0.4% divergence (two substitutions) in the LSU D1/D2 domains and 2.3% divergence (13 substitutions) in the ITS regions. The distinguishing morphological characteristics of the three new species, with respect to closely related taxa, are discussed. The identification of these new taxa significantly increases the number of Bannoa that have been described on the surface of plant leaves. Additionally, a key for the identification of Bannoa species is provided.